SOCIAL MEDIA MARKETING INFLUENCE ON CONSUMER PURCHASE INTENTION AT KOPISAA - Fauzi N. J. Usman; Maximilian M. J. Kapa; Yacobus C. W. Siubelan (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2025)
Technological developments in Indonesia show that digital marketing and social media marketing have developed rapidly in Indonesia, but in Kopisaa only around 20% - 30% of social media followers often interact so it is not possible to know specifically the increase in purchasing intention that occurred. Therefore, this study aims to determine the social media marketing influence based on the aspects of Context, Communication, Collaboration, and Connection on the purchasing intention of Kopisaa consumers. This study is quantitative and uses a non-probability sampling technique with a purposive sampling method so that it uses data from 93 respondents with certain criteria obtained through a questionnaire. Data analysis was carried out by Structural Equation Modelling (SEM) model test to analyze one or more variables simultaneously. The results showed that 59.4% of the Purchasing intention variables were influenced by the aspects of Context (X1), Communication (X2), Collaboration (X3), and Connection (X4). The hypothesis test conducted showed that the Context and Connection aspects had a positive and significant influence on the purchasing intention of Kopisaa consumers, while the Communication and Collaboration aspects had a positive but insignificant influence. These results confirm that marketing through social media has a positive influence on consumer purchasing intention.